REVITALISASI NILAI-NILAI AGAMA ISLAM DALAM PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI - Tb. Chaeru Nugraha; H.U. Jalaludin (Jurnal Penelitian Agama, 2011)
n this study, the author tried to compare the internalization of concepts and methods in the life of Islam at the time of Prophet Muhammad and at present time. At the level of concepts, the values of Islam duning the life of Prophet Muhammad were still pure and clear that it could enlighten the community. Meanwhile, at present, some of the values of Islam have been infiltrated by the values of secularism, materialism. In such a case, ft is necessary to revitalize the pure Islamic values as the foundation of life, including the intra-and inter-religious tolerance. Through leaming the smart (specific, measurable, achievable, relevant, and time framed) it is expected f pure Islam will be easily realized. In one hand, evel of methodology, the internalization of Islamic values at the time Prophet was performed comprehensively (kaffah). On the other hand, at present time, the method Of internalization is performed partially and not integrated. It is expected evitalization of the concepts and methods of internalization of Islamic values will be as closed as the methods applied at the time of Prophet Muhammad. First, the revitalization of the concept of ageedah and Islamic values should cover ali aspects of life. Second, the method of intemalizing the values of Islam should touch the Cognitive, affective, and psychomotor aspects. Third, techniques of internalization hould be creative and innovative, using a various media, including insemination technology.